Zarządzanie strategiczne jako proces : studium przypadków - Kaleta, Andrzej (Strategic Management as a Process : Case Studies, 2009)
The article titled "Strategic management as a process - case studies" is the analysis of the methods of strategic management used in the studied enterprises. It shows the unsatisfactory continuity in creating the strategic concepts and their limited influence on the operating of the companies. The only chance to eliminate these problems is transforming the strategic management into the continuous process, where the strategic analysis is done incessantly and with the mutual connection with the strategy and the process of implementing it, as well as developing the strategic assumptions. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 49-57